2019
DOI: 10.1007/s40430-019-1813-9
|View full text |Cite
|
Sign up to set email alerts
|

EDM performance of Inconel 718 superalloy: application of multi-walled carbon nanotube (MWCNT) added dielectric media

Abstract: Electro-discharge machining (EDM) is very promising non-traditional machining route to cut 'difficult-to-machine' materials like Inconel 718 superalloy. However, low material removal efficiency and inferior surface integrity restricts EDM application on Inconel 718. In order to improve EDM performance, multi-walled carbon nanotube (MWCNT) dispersed into kerosene is explored as dielectric media. Experiments are conducted by varying peak discharge current with a fixed concentration of MWCNT (0.5 g/l) added to ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Owing to the release of trapped gases during the solidification, pockmarks appeared on the machined surface. Molten debris solidifies and spread as globules on the machined surface due to surface tension [35]. The SEM images of the test piece which were showing highest MRR (Ton=113 µs, Toff=54 µs, Ip=11 A, Uw=4 m/min) depicted in Figure 7 It was perceive that at the highest value of MRR (3.073 mm 3 /min), wide and deep craters has developed because of higher pulse duration (113 µs) and peak current (11 A), depicts in Figure 7.…”
Section: Microstructure Characterization Of Surfacementioning
confidence: 99%
“…Owing to the release of trapped gases during the solidification, pockmarks appeared on the machined surface. Molten debris solidifies and spread as globules on the machined surface due to surface tension [35]. The SEM images of the test piece which were showing highest MRR (Ton=113 µs, Toff=54 µs, Ip=11 A, Uw=4 m/min) depicted in Figure 7 It was perceive that at the highest value of MRR (3.073 mm 3 /min), wide and deep craters has developed because of higher pulse duration (113 µs) and peak current (11 A), depicts in Figure 7.…”
Section: Microstructure Characterization Of Surfacementioning
confidence: 99%
“…Thrinadh Jadam et al added multi-walled carbon nanotubes (MWCNT) at a concentration of 0.5 g/l to kerosene as a dielectric for EDM and conducted experiments by varying the peak discharge current. The experimental results show that the use of MWCNT hybrid dielectric can signi cantly improve the machining performance compared to conventional EDM [21] . Yi Jiang et al used air and argon as gas media for EDM (Air-EDM and Ar-EDM, respectively) for the electrical discharge machining of TC4 titanium alloy and Cr12 steel.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, dielectric fluid containing nanotubes/grapheme sheets is expected to have better thermal conductivity and enhance the machining performance and surface quality [27].…”
Section: Introductionmentioning
confidence: 99%
“…Obtained results have shown that Ton lower than 125 µs would be helpful in the minimization of micro-crack and RLT. Jadam et al [27] used MWCNT amount in the dielectric fluid to investigate nickel-based super-alloys EDM performance. The effect of current was also studied along with the MWCNT amount.…”
Section: Introductionmentioning
confidence: 99%